A novel use of etched multi‐mode fibre as magnetic field sensor. Issue 6 (1st December 2017) - Bhardwaj, Vanita; Singh, Vinod Kumar
Abstract : In this study, an optical fibre magnetic field sensor is experimentally demonstrated using chemical etched multimode fibre sandwiched between two single mode fibres. The obtained result of the magnetic field and refractive index response shows that the decreasing fibre diameter in the sensing region plays an important role to enhance the sensitivity of the device. The magnetic field sensing is based on a tunable refractive index (RI) property of magnetic fluid infiltrated into the capillary tube. The sensing system is verified by testing RI of different concentrations of sodium chloride (NaCl) solution before sealing in capillary tube. Experimental results show that the sensor with taper fibre diameter of 45 µm has relatively high magnetic field sensitivity of ∼0.993 dB/mT ranging from 0 to 6 mT. The proposed devices find potential applications in magnetic field sensing.